Pengaruh Biaya Operasional dan Arus Kas Terhadap Profitabilitasn Pada UD Sari Bumi Probolinggo - Junaidi Junaidi (Ecobuss, 2016)
The aim of study is to analyse the effect of operational cost on profitability (return on assets) and cash flow effect on profitability (return on assets). This type of research is descriptive, the research variables consists of of operational cost (X1), cash flow (X2), and profitability (Y). The data used in this study is the financial statements of the year 2009 – 2013, while the data analysis used weredescriptive quantitative data in such as regression analysis of multiple.Based on this research progress of operational cost and cash flows affecting the profitability of UD Sari Bumi, based on simple linier regression analysis obtainedY = 132,35 – 0,23X1 - 0,16X2, the coefficient of the independent variable X1 (Operational Costs) amounted to -0.23 and independent variables X2 (Cash Flow) that is equal to -0.16.Of the calculation results of hypothesis test (t test) showed influential significantly toprofitability UD Sari Bumi Probolinggo" . Key word: Operational cost, cash flow, profitability.